Public Relations Strategy Of PT Pertamina Geothermal Energy Area Ulubelu In Improving Image Through Media Activities : (Public Relations Strategy Research Center of PT Pertamina Geothermal Energy Area Ulubelu, Tanggamus Lampung) - Destiana, Destiana; M Denu Poyo (Cita konsultindo, 2023)
PT Pertamina Geothermal Energy Area Ulubelu as a state-owned company engaged in geothermal has the responsibility for the publication in order to show the company's development in front of the public and also to enhance the company's image itself which is realized through the company's Public Relations strategy. This study aims to determine the Public Relations Strategy of PT Pertamina Geothermal in carrying out Media Activities as a form of responsibility while enhancing the company's image. This type of research is descriptive qualitative, to describe in depth and detail the object of research. The results showed that the Public Relations of PT Pertamina Geothermal Energy Area Ulubelu was published through the official website, brochures, mass media, and social media.